How did the animal virus that led to COVID-19 jump species? - International Livestock Research Institute (2022)
How did a coronavirus that infected bats come to infect humans? Watch this short animation to learn how and why viral zoonoses naturally occur and visit ilri.org/zoonoses to learn more about our work on zoonotic pathogens. This whiteboard animation was created by Annabel Slater / ILRI for the second anniversary of the COVID-19 pandemic. Music: Welcome Back by mobygratis.com